Assessing the validity of Task Analysis as a quantitative tool to measure the efficacy of rehabilitation in brain injury. (2nd January 2017) - Velikonja, Diana; Oakes, Jill; Brum, Christine; Sachdeva, Muskaan
Abstract: Background : Inpatient rehabilitation with patients who have sustained an acquired brain injury (ABI), including traumatic brain injury (TBI), focuses on improving performance in activities of daily living (ADLs). Although not studied to date in patients with ABI/TBI, Task Analysis (TA) integrates assessment and the prompting/cueing levels required to complete various tasks, with the goal to achieve effective skill acquisition and rehabilitation planning. TA has demonstrated efficacy in teaching life skills in individuals with developmental disabilities and in this study is applied to teaching ADL skills in ABI/TBI rehabilitation. Primary objective : To validate the use of TA in measuring progress in teaching ADLs by comparing it with three common ADL measures: Functional Independence Measure, Barthel Index and Klein-Bell. Methods : Twenty-four inpatients were administered the Functional Independence Measure (FIM), Barthel Index (BI) and the Klein-Bell ADL Scale (KB) TA within 72 hours of admission, at 4 weeks and within 72 hours of discharge, for showering and dressing tasks. A repeated measures ANOVA compared scores across the four measures, at three time points, for both tasks. Conclusion : Concurrent validity of TA in measuring improvements in the ADL tasks was established. Improvements were associated with reductions in supervision and disability levels. TA was shown to be an effective evaluation and teaching strategy during rehabilitation, with demonstrated reductions in disability and supervision levels.